Public revenues and public expenditure nexus: evidence from Eurozone heterogeneity - Olgica Glavaški; Emilija Beker Pucar; Stefan Stojkov (Anali Ekonomskog fakulteta u Subotici, 2022)
After the global economic crisis, a broad consensus has emerged that membership in the Eurozone exerts a strong pressure on fiscal policy, since it is characterized by the dichotomy of common monetary policy and heterogeneous fiscal policies. In this paper are analyzed the performances of fiscal policies, highlighting the nexus between the public revenues and public expenditure from the angle of 19 Eurozone economies in the period 2010q1-2020q4. The research is based on Dumitrescu & Hurlin (2012) and Juodis, Karavias & Sarafidis (2021) Granger non-causality tests in macro panels in order to test causality direction, as well as Westerlund error-correction-based panel cointegration test to analyze fiscal sustainability. Having in mind heterogeneity and divergency of the Eurozone members, sub-samples were estimated, concerning the core, the periphery and the emerging Eurozone economies. The results imply that all Eurozone economies achieve weak fiscal sustainability, while all economies from the group of Eurozone periphery applied “tax and spend” hypothesis. The empirical finding could be related to the fact that Eurozone periphery economies were hit harder by the global and sovereign debt crisis, and that implemented austerity and bail-out programs were adequate, thus resulting in sustainable fiscal position and convergence towards the Eurozone core economies.